(untitled) - Adams, Laurie schneider (Boston, 2005)
This volume focuses on the Western canon of art history and presents a chronological narrative from prehistory to the present. The text Art introduces readers to the complexity of images while surveying the major works of Western art. It encourages readers to experience the history of Art as a dynamic narrative, creating a "dialogue" between modern viewers and their past. This text refers to an out of print or unavailable edition of this title.
Keywords: Nghệ thuật, Art; Lịch sử,History